Improvement of local microcirculation through intermittent Negative Pressure Wound Therapy (NPWT). Issue 4 (November 2018) - Sogorski, A.; Lehnhardt, M.; Goertz, O.; Harati, K.; Kapalschinski, N.; Hirsch, T.; Daigeler, A.; Kolbenschlag, J.
Abstract: Background: Negative Pressure Wound Therapy (NPWT) is widely used across different kinds of surgical disciplines. A controversial debate was raised by diverging results from studies that were conducted to examine the impact of NPWT on local perfusion. Thus, there is a lack of evidence for one important underlying factors that influences the physiology of wound healing under an applied NPWT-dressing. Objective: To investigate the immediate local perfusion changes due to an applied intermittent NPWT protocol. Material and methods: A NPWT dressing was applied to the antero-lateral thigh of seven healthy volunteers with two probes of both pressure and microcirculatory measuring devices. One of each probe was placed under the NPWT dressing, the other one in close proximity next to it. A protocol consisting of two cycles of 10 min of −125 mmHg pressure, followed by 10 min of 0 mmHg pressure was applied. Measurements of local pressure to the underlying tissue, as well as microcirculatory changes were performed continuously. Results: Applied vacuum caused compressional forces (27.33 mmHg, p < 0.05) towards the underlying tissue. Blood Flow was increased after both suction periods (+52.5%, +108.7%; p < 0.05) and continued increasing until the end of measurements (+145.3%). This was accompanied by significant increase in Oxygen Saturation (+21.6%; p < 0.05) and Relative Hemoglobin Content (+16.7%). Red Blood Cell Velocity was found to be increased without statistical significance. Next to the dressing, changes were also significant but less pronounced. Conclusion: Intermittent NPWT improves local microcirculation with consecutive enhancement of oxygen supply. Highlights: Intermittent NPWT significantly improves local cutaneous perfusion with consecutive enhancement of oxygen supply. NPWT causes significant compressional forces towards underlying tissues. Combined Laser-Doppler and tissue spectroscopy offers comprehensible real time perfusion analysis in NPWT.